2022
DOI: 10.1002/mrm.29259
|View full text |Cite
|
Sign up to set email alerts
|

RF coil design for accurate parallel imaging on 13C MRSI using 23Na sensitivity profiles

Abstract: To develop a coil-based method to obtain accurate sensitivity profiles in 13 C MRI at 3T from the endogenous 23 Na. An eight-channel array is designed for 13 C MR acquisitions. As application examples, the array is used for two-fold accelerated acquisitions of both hyperpolarized 13 C metabolic imaging of pig kidneys and the human brain.Methods: A flexible coil array was tuned optimally for 13 C at 3T (32.1 MHz), with the coil coupling coefficients matched to be nearly identical at the resonance frequency of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…While this work is based on large single‐ or dual‐loop coils (rprefix≈10$$ r\approx 10 $$ cm), often coil arrays of multiple smaller loops are used to improve the detection sensitivity without limiting the field of view, 21 or for making use of parallel imaging 38 . For hyperpolarized 13$$ {}^{13} $$C body imaging, the individual loops of such arrays typically have radii around 5 cm 38,39 (or corresponding rectangular sizes with similar areas 40 ), for which sample noise still slightly exceeds coil noise at 1.5T (Figure 4). However, our Q‐ratio measurements showed that the 16 MHz single‐loop coil with 10 cm radius is already at the limit and hence coil arrays with small loops might be coil noise‐dominated and therefore not beneficial at lower fields.…”
Section: Discussionmentioning
confidence: 99%
“…While this work is based on large single‐ or dual‐loop coils (rprefix≈10$$ r\approx 10 $$ cm), often coil arrays of multiple smaller loops are used to improve the detection sensitivity without limiting the field of view, 21 or for making use of parallel imaging 38 . For hyperpolarized 13$$ {}^{13} $$C body imaging, the individual loops of such arrays typically have radii around 5 cm 38,39 (or corresponding rectangular sizes with similar areas 40 ), for which sample noise still slightly exceeds coil noise at 1.5T (Figure 4). However, our Q‐ratio measurements showed that the 16 MHz single‐loop coil with 10 cm radius is already at the limit and hence coil arrays with small loops might be coil noise‐dominated and therefore not beneficial at lower fields.…”
Section: Discussionmentioning
confidence: 99%
“…The image reconstruction methods used in human [1- 13 C]pyruvate studies have typically been conventional methods (e.g., FFT, non-uniform FFT, or equivalent). The incorporation of accelerated imaging and advanced reconstruction methods including parallel imaging 10,57,87 and compressed sensing 7 has also been applied in human studies for improved spatial resolution, temporal resolution, and coverage, but have the potential for additional artifacts as well as SNR losses because of ill-conditioning of the reconstruction (e.g., g-factor). The majority of published studies do not use accelerated imaging indicating the resolution and coverage achievable without acceleration is currently adequate for successful data collection.…”
Section: Acquisition and Reconstruction Methodsmentioning
confidence: 99%
“…For HP 13 C MRI of the human brain, the majority of studies have also used 2D (slice selective) acquisitions, 10–12,14,16,28,33,40–41,44,51,53,60 with a trend toward volumetric coverage using 2D multislice metabolite‐specific imaging. Three dimensional metabolite‐specific imaging of the whole brain, with phase encoding of the slice direction, 34,57 has been shown to provide similar SNR efficiency 88 compared with multislice imaging. A number of studies have used MRSI 5,6,29,31–33,50,55 resulting in a spectrum from each voxel, which has the advantage of not requiring a priori information about which peaks to encode.…”
Section: Acquisition and Reconstructionmentioning
confidence: 99%
See 2 more Smart Citations